Context-Aware Adaptation in DySCAS - Anthony, Richard; Chen, Dejiu; Pelc, Mariusz; Persson, Magnus; Torngren, Martin (Electronic Communications of the EASST, 2009)
DySCAS is a dynamically self-configuring middleware for automotivecontrol systems. The addition of autonomic, context-aware dynamic configurationto automotive control systems brings a potential for a wide range of benefits in termsof robustness, flexibility, upgrading etc. However, the automotive systems representa particularly challenging domain for the deployment of autonomics concepts, havinga combination of real-time performance constraints, severe resource limitations,safety-critical aspects and cost pressures. For these reasons current systems are staticallyconfigured. This paper describes the dynamic run-time configuration aspectsof DySCAS and focuses on the extent to which context-aware adaptation has beenachieved in DySCAS, and the ways in which the various design and implementationchallenges are met.